Perlindungan Hukum Terhadap Hak Politik Penyandang Disabilitas Dalam Pemeilihan Umum Presiden - Polin, Filmon M. (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
General elections are at the core of a democratic system involving the participation of every citizen. However, people with disabilities often face challenges in accessing and exercising their political rights. This article explores the legal framework governing and protecting the political rights of people with disabilities in the context of general elections in Indonesia. By analyzing laws, regulations, and implementation practices, this research aims to provide an in-depth understanding of the legal protection afforded to people with disabilities in the electoral process. This study is of a normative legal research type. The legal materials used in this research consist of three sources: primary, secondary, and tertiary legal materials. The data collection techniques used include a statutory approach, conceptual approach, document study, and quotation cards. The results classify the forms of legal protection for the political rights of people with disabilities into two categories: (a) Legal protection of the rights of people with disabilities in the form of Law Number 8 of 2016 concerning People with Disabilities, Regional Regulation of Bali Province Number 9 of 2015, and Regional Regulation of East Nusa Tenggara Province Number 6 of 2022; and (b) Legal protection of the rights of people with disabilities in the form of special facilities provision for people with disabilities in participating in presidential elections. The legal protection of the political rights of people with disabilities in general elections in Indonesia requires a holistic and sustainable approach. Therefore, the participation of all stakeholders, including the government, civil society organizations, and the private sector, is needed.